Hydroxychloroquine use in the COVID-19 patient - Littlejohn, Emily (Cleveland Clinic Journal of Medicine, 2020)
Hydroxychloroquine (HCQ) has multiple potential antiviral mechanisms of action that differ according to the pathogen studied (eg, Chikungunya, Dengue virus, human immunodeficiency virus, poliovirus, Zika virus). Data on HCQ for treatment of coronavirus disease 2019 (COVID-19) are rapidly evolving. To date, there is no evidence from randomized controlled trials that HCQ, or any single therapy, improves outcomes in patients infected with COVID-19. There are also no clinical trial data supporting prophylactic HCQ therapy in COVID-19. Use of HCQ in patients with COVID-19 is being investigated for prophylaxis, postexposure prophylaxis, and treatment.